Certified in Risk and Information Systems Control (CRISC) Exam Tips. - Brennen, Jerod (linkedin.com, 2021)
Prepare for the Certified in Risk and Information Systems Control (CRISC) certification exam. This course offers an introduction to the four-part CRISC Cert Prep series.